2017
DOI: 10.1111/1346-8138.14069
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic effect of hydroxychloroquine on lupus alopecia

Abstract: Lupus alopecia is usually difficult to treat. We report a case of a 40-year-old woman with Sjögren's syndrome and atopic dermatitis who presented with discoid lupus erythematosus on the forearms and lupus erythematosus profundus with alopecia involving the scalp. A biopsy specimen taken from the discoid lupus erythematosus lesion on the forearm further exhibited a xanthomatous reaction, which however was not detected in another specimen from the lupus erythematosus profundus on the scalp. Treatment with oral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In case reports, treatment with HCQ as monotherapy or in combination with other treatments resulted in improvement in alopecia secondary to variants of CLE, including DLE, LEP, and tumid LE. 12,20,28,30,44,[57][58][59] It is important to note that HCQ above a dose regimen of 5 mg/kg is associated with significant ocular toxicity and should be avoided. 60…”
Section: Corticosteroids and Antimalarialsmentioning
confidence: 99%
“…In case reports, treatment with HCQ as monotherapy or in combination with other treatments resulted in improvement in alopecia secondary to variants of CLE, including DLE, LEP, and tumid LE. 12,20,28,30,44,[57][58][59] It is important to note that HCQ above a dose regimen of 5 mg/kg is associated with significant ocular toxicity and should be avoided. 60…”
Section: Corticosteroids and Antimalarialsmentioning
confidence: 99%
“…Hamilton et al 7 treated DLE‐induced hair loss by oral administration of prednisone, hydroxychloroquine; topical use of clobetasol and tacrolimus; and local injection of triamcinolone to achieve hair regeneration. A patient with hair loss diagnosed with DLE showed a reduction in skin lesions after treatment with a small dose of hydroxychloroquine (200 mg/day) and also had new hair appearing in the alopecia area 8 . Yokogawa et al 9 confirmed in a double‐blind, randomized controlled trial that hydroxychloroquine remarkably improved the clinical symptoms of patients compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…CA from CCLE is seven times more common in women. CA is generally permanent and irreversible, 2 although hair regrowth has been noted in some patients with CA secondary to CCLE 3‐5 . We present three cases of CCLE where prompt treatment led to significant hair regrowth.…”
Section: Figurementioning
confidence: 90%